WORLDVIEW IN MAYA ANGELOU’S POEMS: LUCIEN GOLDMANN’S GENETIC STRUCTURALISM APPROACH - Lukitaning Nur Jayanti (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
A work of literature was born inside society as a reflection of the author’s imagination and representation in their life (Zimmerman & Goldmann, 2013). Thus it can be said that the background of the authors as a member of their society can influence the works that they create as it consists of the social reality of the life they lived. Maya Angelou is one of them, as she had influenced her literary works, as it represented through her thought and ideology as an individual. As David Kelly states in his essay “Poetry for Student” (1997), said that “a particular world-view will express itself in particular music (poetic) sensibility. Angelou was writing from her gut experience, not from a study of ethnomusicology, but a good poet’s instinct is valuable precisely for the truths it somehow knows.” Therefore, the purposes of the study are to test the validation of the Goldmann theory of Genetic Structuralism in understanding the Worldview approach and to verify David Kelly’s statement in his personal opinion of Maya Angelou. The research was conducted by analyzing Maya Angelou’s three poems in the eyes of the Genetic Structuralism point of view by Lucien Goldmann. There were two different sources of the data taken for this study. As a result, it shows that a collective subject that all human behavior with historical dimensions is connected, and worldviews are constructed by the coherence of the context within literal work with real-life social contexts of the author, have been approved and validated and that they can be viewed in Maya Angelou’s works.